2021
DOI: 10.1021/acsomega.0c06165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Disease State on the Pharmacokinetics of Bedaquiline in Renal-Impaired and Diabetic Rats

Abstract: Bedaquiline (TMC-207) is a key anti-tubercular drug to fight against multidrug resistance tuberculosis. Little information is available till date on the impact of any disease state toward its pharmacokinetic behavior. The present research work aimed to investigate the effect of renal impairment and diabetes mellitus on the oral pharmacokinetics of bedaquiline in the rat model. Renal impairment and diabetes mellitus were induced in the Wistar rat model separately using cisplatin and streptozotocin, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
(68 reference statements)
4
7
0
Order By: Relevance
“…Serum levels of urea and creatinine are known to rise during renal impairment. 21 We also observed substantial augmentation of their levels by 3.5-and 4.4-fold, respectively, compared to normal rats (Figure 2A,B). Additionally, altered histopathological features of the kidney, like inflammatory cell infiltration and desquamation of tubular epithelial cells, verified the fact of kidney injury introduction (Figure 2C,D).…”
Section: Pharmacokinetics Of Eidd-1931 In the Kidney Injury Statesupporting
confidence: 52%
See 2 more Smart Citations
“…Serum levels of urea and creatinine are known to rise during renal impairment. 21 We also observed substantial augmentation of their levels by 3.5-and 4.4-fold, respectively, compared to normal rats (Figure 2A,B). Additionally, altered histopathological features of the kidney, like inflammatory cell infiltration and desquamation of tubular epithelial cells, verified the fact of kidney injury introduction (Figure 2C,D).…”
Section: Pharmacokinetics Of Eidd-1931 In the Kidney Injury Statesupporting
confidence: 52%
“…The kidney injury was induced in 10 rats by treating cisplatin (7 mg/kg) via the intraperitoneal route. , Normal saline was used as a vehicle to prepare the cisplatin dose. After 72 h, a blood sample was obtained from all the animals to measure serum creatinine and urea levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood (∼120 μL) was withdrawn at each time point from the retro-orbital plexus. Then, the sample was centrifuged at 8000 rpm for 10 min to take out 50 μL of plasma and kept at −80 °C until analysis. , On the day of analysis, the plasma samples were thawed, processed, and analyzed as mentioned above for rottlerin.…”
Section: Materials and Methodsmentioning
confidence: 99%
“… 73 Animal models in rats have shown that bedaquiline blood concentrations are altered in the presence of DM, making a dose adjustment necessary to avoid therapeutic failure. 73 , 74 However, recent evidence from 2021 that compares bedaquiline treatment in TB patients vs TB-DM patients has shown that administering the same dose for both groups results in similar TB outcomes. 75 Similar studies need to be conducted for pretomanid.…”
Section: Tuberculosis and Diabetes: Twin Epidemicsmentioning
confidence: 99%